The Profile of Medicine Storage at Pacongkang Health Center, Liliriaja District, Soppeng Regency - Asrina, Rina; Angreni, Riri (Jurnal Farmasi Sandi Karsa, 2021)
The storage of drug is one of management activities toward pharmaceutical preparation in order that the quality of the drug can be ensured and avoided by Physical damage, also chemistry based on the requirement decided. This research has aim to know how the process of drug storage at the Pacongkang public health center in Liliriaja distric Soppeng regency. This research used descriptive method by using Gutman scale. Based on the result of this research, it can be concluded that the drug storage at the Pacongkang public health center, which doesn’t meet with the requirements caused by the facilities and infrastructure of the drug storage with percentage 44,44%. Meanwhile, The drug storage which suitable with the requirement with percentage 70,00% so it can be inferred that the drug storage at Pacongkang public health center doesen’t meet with the requirements yet.